Faktor Keperilakuan dan Perilaku Kecurangan Akademik: Peran Niat sebagai Variabel Mediasi - Rika Candra Wandayu; Bambang Purnomosidhi; Abdul Ghofar (Riset Akuntansi dan Keuangan Indonesia, 2019)
The purpose of this study is to examine the effect of rationalization reflected using the Theory of Planned Behavior and students' ethical beliefs about the intention to commit academic fraud. In addition, it examines the influence of pressure, intentions, and opportunities on academic fraud. The data of this study was obtained by distributing 229 pieces of questionnaire to Postgraduate students of  Faculty of Economics and Business, Brawijaya University Malang who know about academic fraud. This study uses WarpPLS in assessing the validity and the reliability of the data. The results show that rationalization has a negative effect on students 'intentions to commit academic fraud even though rationalization is high. However, it does not influence students' intention to commit fraud because of the high ethical beliefs of students that affect the fraudulency. In addition, even though rationalization has no effect, students receive high pressure and have big opportunities to commit fraud, so the intention to commit fraud arises, making academic fraud possible to happen.